Prevalence of Depression among Patients with Type-1 and Type-2 Diabetes Mellitus - Muhammad Usman Mumtaz, Shanza Sarfraz, Muhammad Usman Musharraf, Amna Rizvi, (Pakistan Journal of Medical & Health Sciences, 2023)
The diabetic patients are more likely to experience depression. The study's objective was to determine the depression prevalence in newly diagnosed patients with type-I (T1DM) and type-II (T2DM) diabetes, as well as the relationship between these symptoms and several independent clinical and sociodemographic variables. Place and Duration: Study took place in the Department of Endocrinology and metabolism in Services Hospital Lahore, Pakistan for six months of duration from January 2017 to June 2017. Methods: A total of 320 patients included in the study, including two control groups of 180 people without diabetes and 75 patients in each group with T1DM and T2DM. The clinical, biochemical and sociodemographic characteristics of the patients were assessed and Beck Depression Inventory (BDI) was used to assess the symptoms of depression among patients. The association between the scores of BDI and independent factors such age, sex, mean arterial pressure, diabetes duration, BMI, diabetic complications and HbA1c level were assessed in the logistic regression analysis. Results: Compared to controls, females and males with T1DM and T2DM had significantly higher mean BDI scores. Females had depression symptoms more frequently than males diagnosed with diabetes mellitus. Patients with T1DM reported depressive symptoms among 20% of females and 5.7% of males, whereas those with T2DM have depression among 40.6% of women and 23.2% of men. The depression increased with age in patients with T1DM and T2DM, their HbA1c level rises, and they experience more complications. Women with T2DM also have a three-fold high risk of developing depressive symptoms than males. Conclusion: In conclusion, diabetic patients are more likely to experience depression in comparison to non-diabetics. 13.3% of T1DM patients and 30.7% of the T2DM patients having depressive symptoms. HbA1c level, age and the occurrence of comorbidities all raise the risk of depression in both T1DM and T2DM, and in T2DM depression is gender -specific. Keywords: Depressive symptoms, Beck Depression Inventory, type I and type II diabetes mellitus.